Lyon, Saint-Georges Archéologie, environnement et histoire d'un espace fluvial en bord de Saône - Ayala, Grégoire (Documents d'archéologie française, 2012)
In advance of the construction of an underground parking lot on the edge of the Saint-Georges quarter in the city of Lyon, on the right bank of the Saône, a team of Inrap archaeologists conducted an excavation between 2002 and 2004 with the goal of reconstructing the nature of the human installation from the beginning of Antiquity. Strongly supported by previous research and enriched by several complementary disciplines, the long and complex preventive excavation of the Parc Saint-Georges provided an opportunity to reconstruct the history of a riverbank with a difficult natural topography, which was gradually liberated from the river course, while not completely breaking from its influence. At this site, we find key evidence for the genesis of the formation of the alluvial plain of Lyon. At the end of the Protohistoric period, this was the location of the confluence of the original Rhone and Saône rivers, and then that of the new course of the Saône. The vitality of the fluvial network and port activities at Lugdunum are clearly illustrated by the discovery of a pier in association with a ferry dated to the end of the 1st century ad, and five heavy-tonnage barges dated to the 2nd and 3rd centuries. After a period of decreased occupation during the Early Middle Ages, the sector was progressively urbanized starting in the 12th century. At the center of the excavation, a zone with no construction was to be the future site of the port of Sablet. In the 16th century, this fluvial port was well established within the urban framework of the quarter. Seven fishwell boats provide evidence of commercial fishing activities. Significant changes were made in the second half of the 17th century in order to create a monumental port. A boat, which perhaps served for the transport of heavy merchandise, is dated to the middle of the 18th century. Until the end of the 19th century, the construction of the Fulchiron quay deprived the sector of direct access to the river, the bank was modified to accommodate the fluvial port of the quarter, and the environment was composed of "waterfront" houses. The significant historical data presented in this publication, obtained through a thorough exploitation of the information contributed by this excavation, represents a decisive advance in archaeological research, allowing a reconstruction of the early evolution of a major fluvial zone of the city of Lyon.